Genetic and environmental effects on age at first farrowing in sows in southeastern Brazil - Cavalcante-Neto, A.; Lui, J. F. [UNESP]; Sarmento, J. L. R.; Ribeiro, M. N.; Fonseca, C.; Tonhati, Humberto [UNESP]; Monteiro, J. M. C.; Lara, M. A. C.; Queiroz, S. A. [UNESP] (Funpec-editora, 2011)
We evaluated genetic and environmental factors affecting age at first farrowing of sows in the Brazilian southeast. For this purpose, 466 observations regarding the age at first farrowing were made for Dalland-C40 (c) animals belonging to two herds. The effects of the environmental factors on this trait were assessed by means of a model that included, as random effects, the influence of the sow's father and mother and, as fixed effects, the influence the year of birth, the herd and the birth season, along with the covariable litter size at birth. The variance components were estimated using the derivative-free restricted maximum likelihood method. The estimated mean was 354.8 +/- 25.87 days, with a coefficient of variation of 7.29%. Significant effects on the trait were observed for the herd, the year and the season of birth; but a linear effect of litter size at birth on the age at first farrowing was not observed. The boar did not significantly contribute to the variation occurring among the sows, whereas the sow's mother caused significant variation. The heritability estimate for the age at first farrowing was 0.44 +/- 0.15, which is considered high. We concluded that herd effect and year and season of birth should be taken into consideration for an accurate genetic comparison; consequently, the animals should be joined into contemporary groups.
Keywords: Puberty; Reproduction; Non-genetic factors